Surgical resection for lung cancer: Optimising patient evaluation and recovery - Cavalheri de Oliveira, Vinicius (Curtin University, 2014)
The studies in this thesis evaluated the current physiotherapy practice patterns for people undergoing surgery for lung cancer and, in people following lobectomy for non-small cell lung cancer, investigated impairments in exercise capacity, health-related quality of life, muscle force, physical activity, lung function, dyspnoea and fatigue, and feelings of anxiety and depression; compared exercise responses during a laboratory-based and a field-based exercise test; and investigated the effects of exercise training on the aforementioned outcomes.